Pharmacological Treatment of 22q11.2 Deletion Syndrome-related Psychoses - Boot, E.; Butcher, N. J.; Vorstman, J. A. S.; van Amelsvoort, T. A. M. J.; Fung, W. L. A.; Bassett, A. S. (Pharmacopsychiatry, 2015)
In their recent article in Pharmacopsychiatry Verhoeven and Egger report a case series of 28 patients and state that “treatment of psychotic symptoms in patients with 22q11.2 deletion syndrome (22q11.2DS) with quetiapine or clozapine in combination with valproic acid appears likely to be more effective than with other psychotropic compounds”. In this letter, we discuss the limitations of their case series and the lack of evidence for such a sweeping conclusion. In lieu of strong evidence to the contrary, standard pharmacological treatments of psychotic illness in 22q11.2DS remains recommended, with attention to 22q11.2DS-related issues. The latter would include management strategies to help ameliorate the elevated risk of seizures (e. g. when using clozapine), and vigilance for Parkinson’s disease or other potential movement disorders.
Keywords: 22q11 deletion syndrome; antipsychotic agents; psychotic disorders